Pengolahan Sampah di Perguruan Tinggi dan Kontribusinya Terhadap Penurunan Emisi Gas Rumah Kaca - Tuani Lidiawati S (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
The increasing of student number over the past four years urged Surabaya University to develop campus facility that could serve as a learning media for the academic community in the campus and the community around campus. The proposed facility was composting area. Composting area construction was necessary because the accretion of students would be followed by the growing of solid waste generation. The estimation of solid waste that  be carried to composting area had not been done before. This research was conducted with the aim of: 1. Estimating the quantity of solid waste generation that disposed to composting area 2. Calculating the greenhouse gas reduction that can be achieved by solid waste composting. Solid waste estimation was done before separation process in the composting area. Research was done by  survey and observation. Survey area was engineering  faculty. Sampling  for solid waste estimation was undertaken at TG building. The results  indicated that 70 % of the solid waste was anorganic waste and solid waste generation was 25-50 kgs daily. Solid waste composting process was set once in a week which composting period was seven days. The calculation of green house emission was referred to IPCC guidelines. The result of calculation was Surabaya University could contribute to reduce green house gas emission (CH4) about 40,5 kg CH4.